2017
DOI: 10.5152/turkjorthod.2017.17027
|View full text |Cite
|
Sign up to set email alerts
|

Information on the Internet Regarding Orthognathic Surgery in Turkey: Is It an Adequate Guide for Potential Patients?

Abstract: Objective: To evaluate the quality of information on websites regarding orthognathic surgery in Turkey using the DISCERN toolkit.Methods: An Internet search was performed using the Google search engine with the terms "orthognathic surgery", "jaw surgery", "jaw operation", "correcting jaw surgery", and "surgery orthodontics. " The first 25 websites obtained after searching for each term were evaluated. Duplicate websites, advertisements, discussion groups, links to research articles, videos, and images were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Healthcare professionals should be aware of the quality of Internet content because patients’ interest in online health-related information increases [ 28 ]. It has been suggested that most of the information on the Internet is either incomplete or inaccurate mainly in dentistry [ 11 , 17 19 , 29 32 ]. These results also show that the need for the accuracy and reliability of the information on websites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals should be aware of the quality of Internet content because patients’ interest in online health-related information increases [ 28 ]. It has been suggested that most of the information on the Internet is either incomplete or inaccurate mainly in dentistry [ 11 , 17 19 , 29 32 ]. These results also show that the need for the accuracy and reliability of the information on websites.…”
Section: Discussionmentioning
confidence: 99%
“…People want easy-to-access, useful and understandable information through online research [ 19 ]. However, the quality and accuracy of the information that could be derived from the Internet might not be that high.…”
Section: Discussionmentioning
confidence: 99%
“…When the latter was evaluated the reliability of websites on the thumb sucking habit by the DISCERN tool, the highest points obtained from 36 websites was 55 out of 80, and the lowest points was 16 out of 80. Baybek and Tuncer ( 19 ) evaluated the quality of information on webpages on orthognathic surgery in Turkey using the DISCERN toolkit and stated that the quality of information on orthognathic surgery on the internet was low. It was noted that higher quality information was provided by public institutions that are not concerned about profit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the highly subjective nature of the LIDA questions contributed to the less than ideal interrater agreement scores within this study (Bavbek & Tuncer, 2017;Patel & Cobourne, 2014;Prasanth et al, 2018). To improve interrater agreement, it is recommended that more specific guidelines be developed for the LIDA tools accompanied by greater discussion between raters before commencing the website scoring.…”
Section: Study Limitationsmentioning
confidence: 99%